Preclinical studies of RUC-4, a novel platelet αIIbβ3 antagonist, in non-human primates and with human platelets. Issue 2 (28th June 2019) - Vootukuri, Spandana; Li, Jihong; Nedelman, Mark; Thomas, Craig; Jiang, Jiang-Kang; Babayeva, Mariana; Coller, Barry S.
Abstract: Introduction: We are developing the novel αIIbβ3 antagonist, RUC-4, for subcutaneously (SC)-administered first-point-of-medical-contact treatment for ST segment elevation myocardial infarction (STEMI). Methods: We studied the (1) pharmacokinetics (PK) of RUC-4 at 1.0, 1.93, and 3.86 mg/kg intravenous (IV), intramuscular (IM), and SC in non-human primates (NHPs); (2) impact of aspirin on RUC-4 IC50 in human platelet-rich plasma (PRP); (3) effect of different anticoagulants on the RUC-4 IC50 in human PRP; and (4) relationship between αIIbβ3 receptor blockade by RUC-4 and inhibition of ADP-induced platelet aggregation. Results: (1) All doses of RUC-4 were well tolerated, but animals demonstrated variable temporary bruising. IM and SC RUC-4 reached dose-dependent peak levels within 5–15 minutes, with T1/2 s between 0.28 and 0.56 hours. Platelet aggregation studies in NHPs receiving IM RUC-4 demonstrated >80% inhibition of the initial slope of ADP-induced aggregation with all three doses 30 minutes post-dosing, with subsequent dose-dependent loss of inhibition over 4–5 hours. (2) The RUC-4 IC50 for ADP-induced platelet aggregation was unaffected by aspirin treatment (40±9 nM vs 37±5 nM; p = 0.39). (3) The RUC-4 IC50 was significantly higher in PRP prepared from D-phenylalanyl-prolyl-arginyl chloromethyl ketone (PPACK)-anticoagulated blood compared to citrate-anticoagulated blood using either thrombin receptor activating peptide (TRAP) (122±17 vs 66±25 nM; p = 0.05; n = 4) or ADP (102±22 vs 54±13; p <0.001; n = 5). (4) There was a close correspondence between receptor blockade and inhibition of ADP-induced platelet aggregation, with aggregation inhibition beginning with ~40% receptor blockade and becoming nearly complete at >80% receptor blockade. Discussion: Based on these results and others, RUC-4 has now progressed to formal preclinical toxicology studies.